KOMPETENSI, ORIENTASI DAN MINAT KEWIRAUSAHAAN MAHASISWA STMIK STIKOM INDONESIA - Wayan Eny Mariani; Ni Putu Ayu Siska Wulantari (Universitas Pendidikan Nasional, 2020)
Increasing entrepreneurial competence in the workforce can be done from an early age. Both formal and informal education systems can be used as a means to educate and influence young people to have competencies and interests in the field of entrepreneurship. Higher Education as one of the educational institutions has the opportunity to cultivate competence and entrepreneurial interest in students. This opportunity must be utilized so that it can create young entrepreneurs who will later participate in reducing the unemployment rate in Indonesia. STMIK STIKOM Indonesia is an information technology-based high school that encourages students to become entrepreneurs. STMIK STIKOM Indonesia organizes entrepreneurship courses and there is support from entrepreneurial institutions, namely the STIKI Indonesia Business Incubator, which is the umbrella support for entrepreneurship in the academic community at STMIK STIKOM Indonesia. To be able to increase entrepreneurial competence in STMIK STIKOM Indonesia students, research was conducted on the competence and entrepreneurial interest of STMIK STIKOM Indonesia students. This research is a descriptive study using a questionnaire as a research instrument. The data collection technique was carried out by using a purposive sampling method with the criteria of students who had already received entrepreneurship courses. The results of the study found that entrepreneurial competence had a significant effect on the entrepreneurial interest of STMIK STIKOM Indonesia students